Characterization of coccidiosis and evaluation of suggestive cases of subclinical necrotic enteritis in broilers - Fabio Santiani; Rodrigo Otávio S. Silva; Carlos Augusto de Oliveira Júnior; Jéssica Aline Withoeft; Thierry G. Cristo; Leonardo S. Costa; Taís Gaspar; Renata A. Casagrande (Pesquisa Veterinária Brasileira, 2023)
ABSTRACT: This study performed the characterization of coccidiosis in broilers and evaluated the occurrence of suggestive cases of necrotic enteritis (NE), seeking if there is an association between the diseases in Brazilian flocks. Two hundred and fifty-six birds from 32 flocks were evaluated. Macroscopic and histopathological lesions were graduated for coccidiosis and NE. Intestinal content was investigated by polymerase chain reaction (PCR) for seven species of Eimeria and by selective anaerobic culture for Clostridium perfringens and identification of the NetB gene. Flocks positive for coccidiosis represented 93.8%. Macroscopic lesions of coccidiosis were Grade 1 for E. acervulina (27%); E. tenella (9.7%) and E. maxima (8.9%). Histopathological evaluation showed Grade 1 in duodenum (38.2%); jejunum (21.4%); cecum (9.3%) and ileum (5%). PCR demonstrated positivity for E. tenella (21.9%), E. maxima (18.8%), and E. acervulina (3.1%). Suggestive macroscopic lesions of necrotic enteritis ranged from Grade 1 (16%), 2 (23%) and 3 (10,9%). Histopathology indicated the absence of necrosis, showing only hemorrhage in the mucosa and submucosa, with the presence of Eimeria spp. Clostridium perfringens type A netB+ was not isolated, demonstrating that macroscopic lesions found mostly in the jejunum did not characterize NE, based on histopathology and negativity of the NetB gene. The study suggests that, due to the high occurrence of coccidiosis, many macroscopic findings suggestive of NE are, in fact, attributed to atypical lesions caused by the reproduction of Eimeria spp.